Exploring the Role of Bioenergy in Achieving Sustainable Waste Utilization and Promoting Low-Carbon Transition Strategies (International Journal of Scientific Research in Science and Technology, 2024)
The growing global emphasis on sustainable development and carbon neutrality has intensified the need for innovative waste utilization strategies that align with low-carbon transition goals. This study explores the critical role of bioenergy in transforming waste into a valuable resource while promoting sustainable environmental practices. The research delves into the intersection of bioenergy technologies, sustainable waste management, and carbon emission reduction strategies, examining their synergistic potential to achieve a circular economy. Through an in-depth review of literature, this study identifies the current challenges and opportunities in bioenergy production, including its technical, economic, and policy dimensions. Methodologically, the research employs a combination of life cycle assessment, carbon footprint analysis, and case studies to evaluate the impact of bioenergy on sustainable waste utilization and low-carbon transition strategies. The findings reveal that bioenergy systems not only reduce waste accumulation but also significantly mitigate greenhouse gas emissions, contributing to global sustainability goals. However, challenges such as policy inconsistencies, technological barriers, and high implementation costs persist, hindering large-scale adoption. Based on these findings, this paper provides actionable recommendations for policymakers, industry stakeholders, and researchers, emphasizing the integration of bioenergy within circular economy models and the adoption of supportive policy frameworks. The study concludes that bioenergy represents a transformative pathway toward achieving sustainable waste utilization and a low-carbon future, offering a scalable solution to address environmental challenges while fostering economic and social resilience. This research contributes to the growing discourse on bioenergy’s potential and underscores its role as a cornerstone of sustainable development strategies.